Crowdfunding and its Applicability to Entrepreneurial Marketing - Burak Gökkaya (2016)
Crowdfunding aims for the attention of the general public in order to fund a project through the support of numerous individuals. Therefore, it bears a marketing dimension that usually targets initial customers. The concept of entrepreneurial marketing targets the growth of entrepreneurial-oriented firms through conducting effective marketing methods which take constraints and challenges of start-up companies into consideration like the liability of newness and smallness. In this paper it is validated through a conceptual comparative analysis that crowdfunding can be applied to the concept of entrepreneurial marketing as it fulfills the three functions of entrepreneurial marketing and both crowdfunding and entrepreneurial marketing share common characteristics.